PROBLEMATICS OF THE POSITION OF NOTARY IN TECHNOLOGY DEVELOPMENT AND INFORMATION - Sulaiman Khalid, Raden Raihan; Saleh, Moh. (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2023)
In the development of technology and information, digitalization needs to be carried out to support the duties and positions of a notary. As a way of adaptation, notaries can implement cyber notaries with positive benefits. Cyber Notary is a concept of utilizing technology that can assist notaries in carrying out their duties. Although there are many positive benefits, there are also obstacles to its application in Indonesia. The goal to be achieved in this research is to find out the problems faced by notaries in going digital, in order to find solutions in an effort to support the notary's duties. The method used is a normative juridical method, with an approach to related laws, and a conceptual approach. From the research results obtained, it is concluded that there are statutory constraints that are still contradictory in implementing Cyber Notary if it is implemented, it can lead to legal conflicts for notaries. As a solution, harmonization of applicable laws is needed.